Fungal contamination assessment in Portuguese elderly care centers - Viegas, Carla (2014)
Individuals spend 80-90% of their day indoors and elderly subjects are likely to spend even a greater amount of time indoors. Thus, indoor air pollutants such as bioaerosols may exert a significant impact on this age group. The aim of this study was to characterize fungal contamination within Portuguese elderly care centers. Fungi were measured using conventional as well as molecular methods in bedrooms, living rooms, canteens, storage areas, and outdoors. Bioaerosols were evaluated before and after the microenvironments' occupancy in order to understand the role played by occupancy in fungal contamination. Fungal load results varied from 32 colony-forming units CFU m(-3) in bedrooms to 228 CFU m(-3) in storage areas. Penicillium sp. was the most frequently isolated (38.1%), followed by Aspergillus sp. (16.3%) and Chrysonilia sp. (4.2%). With respect to Aspergillus genus, three different fungal species in indoor air were detected, with A. candidus (62.5%) the most prevalent. On surfaces, 40 different fungal species were isolated and the most frequent was Penicillium sp. (22.2%), followed by Aspergillus sp. (17.3%). Real-time polymerase chain reaction did not detect the presence of A. fumigatus complex. Species from Penicillium and Aspergillus genera were the most abundant in air and surfaces. The species A. fumigatus was present in 12.5% of all indoor microenvironments assessed. The living room was the indoor microenvironment with lowest fungal concentration and the storage area was highest.